CD80 on Human T Cells Is Associated With FoxP3 Expression and Supports Treg Homeostasis - Soskic, Blagoje; Jeffery, Louisa E.; Kennedy, Alan; Gardner, David H.; Hou, Tie Zheng; Halliday, Neil; Williams, Cayman; Janman, Daniel; Rowshanravan, Behzad; Hirschfield, Gideon M.; Sansom, David M. (Frontiers in Immunology, 2021)
CD80 and CD86 are expressed on antigen presenting cells (APCs) and their role in providing costimulation to T cells is well established. However, it has been shown that these molecules can also be expressed by T cells, but the significance of this observation remains unknown. We have investigated stimuli that control CD80 and CD86 expression on T cells and show that in APC-free conditions around 40% of activated, proliferating CD4+ T cells express either CD80, CD86 or both. Expression of CD80 and CD86 was strongly dependent upon provision of CD28 costimulation as ligands were not expressed following TCR stimulation alone. Furthermore, we observed that CD80+ T cells possessed the hallmarks of induced regulatory T cells (iTreg), expressing Foxp3 and high levels of CTLA-4 whilst proliferating less extensively. In contrast, CD86 was preferentially expressed on INF-γ producing cells, which proliferated more extensively and had characteristics of effector T cells. Finally, we demonstrated that CD80 expressed on T cells inhibits CTLA-4 function and facilitates the growth of iTreg. Together these data establish endogenous expression of CD80 and CD86 by activated T cells is not due to ligand capture by transendocytosis and highlight clear differences in their expression patterns and associated functions.